Comparison of Simulated Drift Rates of Common ALS-Inhibiting Rice Herbicides to Florpyrauxifen-Benzyl on Soybean. (22nd October 2017) - Schwartz-Lazaro, Lauren M.; Miller, M. Ryan; Norsworthy, Jason K.; Scott, Robert C.
Abstract : Acetolactate synthase- (ALS-) herbicides are among the most commonly used sites of action (SOA) in rice production. Many herbicides used in rice can cause carryover to soybean, which is commonly grown near to or rotated with rice. Florpyrauxifen-benzyl (Rinskor™ Active) brings an alternative SOA to rice production. The objective of this study was to compare the effects of simulated drift rates of florpyrauxifen-benzyl to commonly used ALS-inhibiting rice herbicides on soybean. A field study was conducted at two locations examining five ALS-inhibiting rice herbicides as well as florpyrauxifen-benzyl at a 1/20x and 1/80x simulated drift rate. Crop injury, height, and yield were evaluated at 14, 21, and 35 days after treatment (DAT). Florpyrauxifen-benzyl and bispyribac showed high injury levels at both drift rates. At 35 DAT florpyrauxifen-benzyl caused 76% and 17% visible damage to soybean whereas bispyribac caused 35 and 9% injury at 1/20x and 1/80x, respectively. These treatments resulted in a reduction in soybean height and yield. Although this alternative SOA herbicide in rice may be effective for weed control, our research demonstrates it to be injurious to soybean at both drift rates tested. Thus, proper precautions should be taken to avoid injury by ensuring that the label is followed.